2011
DOI: 10.4049/jimmunol.1002821
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complex-Mediated Cell Activation from Systemic Lupus Erythematosus and Rheumatoid Arthritis Patients Elaborate Different Requirements for IRAK1/4 Kinase Activity across Human Cell Types

Abstract: IL-1R–associated kinases (IRAKs) are important mediators of MyD88-dependent signaling by the TLR/IL-1R superfamily and facilitate inflammatory responses. IRAK4 and IRAK1 function as active kinases and as scaffolds for protein–protein interactions. We report that although IRAK1/4 kinase activity is essential for human plasmacytoid dendritic cell (pDC) activation, it is dispensable in B, T, dendritic, and monocytic cells, which is in contrast with an essential active kinase role in comparable mouse cell types. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 54 publications
4
41
3
Order By: Relevance
“…The inhibitor does not block IL-6 and TNF-␣ production in human dermal fibroblasts, whereas these cytokines are blocked in human monocytes, suggesting cell type-specific requirements for IRAK4 kinase activity in human cells. Our data are not consistent with that of Chiang et al (30), who showed no effect of an IRAK4/IRAK1 dual inhibitor on cytokine production in human monocytes. It is possible that the inhibitor used by Chiang et al (30) was not potent enough to inhibit IRAK4 kinase activity as there was no measurement of pIRAK4 to gauge the extent of inhibition in the monocytes.…”
Section: Irak4 Kinase Activation and Cytokine Inductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The inhibitor does not block IL-6 and TNF-␣ production in human dermal fibroblasts, whereas these cytokines are blocked in human monocytes, suggesting cell type-specific requirements for IRAK4 kinase activity in human cells. Our data are not consistent with that of Chiang et al (30), who showed no effect of an IRAK4/IRAK1 dual inhibitor on cytokine production in human monocytes. It is possible that the inhibitor used by Chiang et al (30) was not potent enough to inhibit IRAK4 kinase activity as there was no measurement of pIRAK4 to gauge the extent of inhibition in the monocytes.…”
Section: Irak4 Kinase Activation and Cytokine Inductioncontrasting
confidence: 99%
“…Our data are not consistent with that of Chiang et al (30), who showed no effect of an IRAK4/IRAK1 dual inhibitor on cytokine production in human monocytes. It is possible that the inhibitor used by Chiang et al (30) was not potent enough to inhibit IRAK4 kinase activity as there was no measurement of pIRAK4 to gauge the extent of inhibition in the monocytes. Indeed, the potency of the inhibitor described by Chiang et al (30) was considerably less potent against IRAK4 and IRAK1 than the inhibitor used in this study, and we have been unable to document inhibition of pIRAK4 in either IL-1␤-stimulated dermal fibroblasts or R848-stimulated primary human monocytes at the concentrations described in that paper (data not shown).…”
Section: Irak4 Kinase Activation and Cytokine Inductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, our data suggest that the kinase activity of IRAK1, rather than IRAK4, is required to mediate this negative regulation of the TLR3-NF-kB pathway. Recently, differences in the requirements for IRAK1/4 kinase activity in IL-1R signaling have emerged between human and mouse immune cells, indicating that the kinase activity is dispensable in IL-1R signaling in human cells (32). We found that blocking the kinase activity of IRAK1 and IRAK4 through the use of the dual IRAK1/4 kinase inhibitor limits the activation of the TLR3 pathway in human cells, because increased IL-6 and IFN-b levels were found in human microglial cells, which were pretreated with the IRAK1/4 inhibitor, following poly(I:C) stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cell (VSMC) proliferation and migration are critical to 1318 tion of IRAK1 and IRAK4 kinase activities would be predicted to leave some degree of host defense intact while still reducing inflammatory responses 18) . A novel cell-permeable benzimidazole compound can act as a potent and selective inhibitor of IRAK1 and IRAK4 and has been tested in plasmacytoid dendritic cells from systemic lupus erythematosus and rheumatoid arthritis patients 19) , human primary small airway epithelial cells in chronic obstructive pulmonary disease 20) , and rat brain hypoxia/ischemiainduced neuronal injury 21) ; however, it has not yet been employed in vascular research. To the best of our knowledge, there are no published studies on the role of IRAK1 and IRAK4 kinase activities in vascular restenosis through the TLR4-mediated NF B signaling pathway.…”
mentioning
confidence: 99%